2002
DOI: 10.1191/1352458502ms787oa
|View full text |Cite
|
Sign up to set email alerts
|

APOE genotypes and disease severity in multiple sclerosis

Abstract: Apolipoprotein E (opoE) is involved in the transport of lipids necessary for membrane repair and is encoded by a gene on chromosome 19q13, a region positive for linkage in two multiple sclerosis (MS) genome-wide screens. The APOE epsilon4 allele confers susceptibility to both familial and sporadic Alzheimer's disease (AD). Carriage of epsilon4 is associated with defective dendritic remodeling in AD, and with unfavorable clinical outcome in head trauma and cerebrovascular disease. According to the results of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 34 publications
2
32
2
3
Order By: Relevance
“…The ε3 allele has been shown to support the effective repair and remodelling after injury by noxious agents in a dose-dependent fashion. In contrast, the ε4 allele may be less effective in these processes of repair after DNA damage, as it does not generally appear to support maintenance of healthy neurites and neuronal cells [1, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40]. This is perhaps due to the variable levels and types of oestrogen receptors within different brain regions and the effect of oestrogen on APO E since the mechanism of this effect may also vary within different regions of the brain [34, 35].…”
Section: Gene Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ε3 allele has been shown to support the effective repair and remodelling after injury by noxious agents in a dose-dependent fashion. In contrast, the ε4 allele may be less effective in these processes of repair after DNA damage, as it does not generally appear to support maintenance of healthy neurites and neuronal cells [1, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40]. This is perhaps due to the variable levels and types of oestrogen receptors within different brain regions and the effect of oestrogen on APO E since the mechanism of this effect may also vary within different regions of the brain [34, 35].…”
Section: Gene Variantsmentioning
confidence: 99%
“…The APO E genetic polymorphism has been shown to modify the risk for a variety of diseases, including breast cancer [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55]. We refer the reader to important reviews by Mahley and Rall [1]and Smith [23], who provide detailed discussions of APO E on the risk of common human diseases and on ageing.…”
Section: Cellular Repair and Protective Mechanismsmentioning
confidence: 99%
“…However, a similar number of studies failed to replicate this association. [16][17][18][19][20][21][22][23] There is moderate evidence supporting a susceptibility locus on chromosome 19; however, this locus is likely to be more distal to APOE than the region considered here. 24,25 The APOE gene is a plausible candidate modifier gene, owing to its involvement in other neurodegenerative disorders, including Alzheimer's disease, 26 Parkinson disease 27 and amyotrophic lateral sclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…The present study did not consider the genotype-phenotype relationship, but in the series in the study by Masterman et al, the APOE ε3/ε4 genotype was more common in severe MS than in benign MS [53]. Fazekas et al found that patients carrying the ε3/ε4 genotype exhibited a significantly higher black hole ratio, demonstrating the disabling effect of the є4 allele [48].…”
Section: V2 Apoementioning
confidence: 62%
“…In contrast, 2.1-7.7% of the patients were genotyped as є4/є4 in studies from Denmark [51,56], Sweden [53] and Kuwait [41]. In general, the low frequency of ɛ4 homozygotes limits the analyses as concerns an independent effect of this genotype.…”
Section: V2 Apoementioning
confidence: 99%